Appropriate Pedagogy to Teach English: Contemporary Tendency Focusing on Non-Native - dos Anjos, Flávius Almeida (English Dapartment, Faculty of Languages and Arts, Universitas Negeri Semarang, 2019)
This paper is about the teaching of English. It takes into account the global role this language gains today, to reflect on how it should be taught. The main objective of it is to defend a current tendency concerning the teaching of English. In the pursuit of an appropriate pedagogy to teach English, I propose the focus on non-native speaker, since we undestand that English is a world language, spoken by a great number of people, from different cultures, what has recreated this language in many aspects. That is why this language should not be only taught based on the hegemonic cultures. The reflection proposed here is, especially, anchored on Freire´s (1996) ideas on education, mainly when he defends learner’s autonomy. Thus, to teach English through an apropriate pedagogy, teachers should allow students to have ownership of it as well, but starting from a local perspective, avoiding, this way, bad feelings on the part of students. Keywords: Pedagogy; English language; non-native